The role of Vanua in climate-related voluntary immobility in Fiji - Yee, Merewalesi; McNamara, Karen E.; Piggott-McKellar, Annah E.; McMichael, Celia (Frontiers in Climate, 2022)
People, communities, and regions around the world are being pushed to adapt as climate-related risks increase. Within both policy and academic literature, the planned relocation of communities is often viewed as an adaptation option of last resort, given that it can lead to losses including to attachment to place, place-based cultural practices, and identity. To date however, few empirical studies have investigated the diverse and context specific reasons for community reluctance to relocate. This is the aim of this study: to examine the motivations behind people’s decisions to remain in locations at risk from climate change. Drawing on ethnographic data from fieldwork undertaken in 2021 in Serua Island, Fiji, this study shows how the concept of Vanua – a Fijian term which refers to the natural environment, social bonds and kinship ties, ways of being, spirituality and stewardship – is used by Indigenous people to resist climate-driven relocation. Through exploring local decision-making, this study contributes to the small body of research on voluntary immobility in the context of climate change. This research also contributes to academic discussions on ‘decolonizing climate change’ from a Pacific perspective while offering a strong empirical basis for critically addressing climate mobility scholarship through Indigenous narratives, values, and worldviews. We highlight that policy and practice must better integrate local understandings of voluntary immobility to avoid potential maladaptation, and loss and damage to culture, livelihoods, and social networks. This can help develop more appropriate adaptation strategies for communities in Fiji and beyond as people move, but also resist mobility, in a warming world.